2022
DOI: 10.1167/iovs.63.5.25
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Deformations Within the Depth of the Lamina Cribrosa in Response to Acute In Vivo Intraocular Pressure Modulation

Abstract: Purpose The lamina cribrosa (LC) is a leading target for initial glaucomatous damage. We investigated the in vivo microstructural deformation within the LC volume in response to acute IOP modulation while maintaining fixed intracranial pressure (ICP). Methods In vivo optic nerve head (ONH) spectral-domain optical coherence tomography (OCT) scans (Leica, Chicago, IL, USA) were obtained from eight eyes of healthy adult rhesus macaques (7 animals; ages = 7.9–14.4 years) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The same patterns of response were detected in the same eyes when examining the LC microstructure in the entire LC depth in a previous study by our group. 30 This indicates that, within the pressure range used in this study, the inherent properties of the LC have a stronger impact on the response pattern than does orientation (anteroposterior vs. centripetal) of the inflicting force. We intentionally selected a pressure range that spanned from the clinical range (high IOP and ICP settings) to an exaggerated physiologic level (highest IOP and ICP) in order to capture the full range of tissue responses.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The same patterns of response were detected in the same eyes when examining the LC microstructure in the entire LC depth in a previous study by our group. 30 This indicates that, within the pressure range used in this study, the inherent properties of the LC have a stronger impact on the response pattern than does orientation (anteroposterior vs. centripetal) of the inflicting force. We intentionally selected a pressure range that spanned from the clinical range (high IOP and ICP settings) to an exaggerated physiologic level (highest IOP and ICP) in order to capture the full range of tissue responses.…”
Section: Discussionmentioning
confidence: 77%
“…In a recent publication, we demonstrated that microstructural deformation in response to pressure modulation occurs throughout the lamina volume and is not captured by anterior lamina analysis. 30 In this study, we evaluated the pore path through the entire LC volume.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, LCPs are visible in 71% of POAG patients compared to 29.3% of controls [ 17 ]. Although several studies have characterized the changes to the LC in patients with glaucoma, few have investigated the associations between LCPs and demographic and ocular characteristics in African-ancestry populations [ 18 , 19 , 20 ]. Existing data show that African-ancestry individuals have a larger total LC area and a greater number of LCPs; however, there is no evidence linking these findings to a higher risk of glaucoma [ 5 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Optical coherence tomography (OCT) has recently become the primary imaging tool for diagnosing IMH and con rming anatomical success after IMH surgery [10]. It clearly displays the retinal microstructure, making it easier to observe changes in external limiting membrane (ELM), ellipsoid zone (EZ) and cone interdigitation zone (CIZ) postoperatively [11,12]. Nevertheless, traditional OCT can only follow the repair of the macular hole from a two-dimensional perspective, which cannot be quanti ed and re ned, making it hard to study the role of retinal vessels and nerves in macular hole repair [11].…”
Section: Introductionmentioning
confidence: 99%